MEMPROGRAMKAN PENGENALAN MANAJEMEN WAKAF DI DESA KAREHKEL, KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Rully Trihantana; Miftakhul Anwar; Rizal Muttaqin (SAHID EMPOWERMENT JOURNAL, 2023)
Waqf, as one of the social and economic institutions of the people, has enormous potential in encouraging efforts to improve the people's economy. As a country with a very large population and a Muslim majority, Indonesia needs to explore and develop the potential of this religious institution. This community service seeks to reintroduce waqf management in Karehkel Village, Leuwiliang District, Bogor Regency. Waqf management needs to remember that in fact a lot of waqf land is only used for worship and does not enter into the practice of muamalah as exemplified since the time of the Prophet Muhammad Sallallahu alaihi Wassalam. The community is interested in waqf management, however, there is still a lot of waqf land that has not been waqf certified, making waqf land management more careful in Karehkel Village. Therefore waqf management is needed and developed to improve the standard of living of the people of Karehkel Village, Leuwiliang District, Bogor Regency.